2005
DOI: 10.2135/cropsci2004.0756
|View full text |Cite
|
Sign up to set email alerts
|

Managing Irrigation and Nitrogen Fertility of Hard Spring Wheats for Optimum Bread and Noodle Quality

Abstract: Although some quality characteristics for the two categories of wheat products are similar, the relative effects End-uses of hard wheat (Triticum aestivum L.) are increasingly of genotype and crop management variables on the two diverse. However, limited understanding of crop management system interactions with genotype exists to tailor production systems for both product categories need better definition. bread and Asian noodle production. Therefore, we evaluated the bread Both protein quantity and quality ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
79
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 39 publications
18
79
0
1
Order By: Relevance
“…The late-season N application has provided clear benefits to the rheological parameters of common improver wheat, thus confirming previous results (Ayoub et al, 1994;Guttieri et al, 2005;Wuest and Cassman, 1992). According to Borghi et al (1995) and López-Bellido et al (2001), as N fertilizer rates increase, a rise in GPC and a corresponding improvement in W and the P/L ratio can be observed.…”
Section: Discussionsupporting
confidence: 86%
“…The late-season N application has provided clear benefits to the rheological parameters of common improver wheat, thus confirming previous results (Ayoub et al, 1994;Guttieri et al, 2005;Wuest and Cassman, 1992). According to Borghi et al (1995) and López-Bellido et al (2001), as N fertilizer rates increase, a rise in GPC and a corresponding improvement in W and the P/L ratio can be observed.…”
Section: Discussionsupporting
confidence: 86%
“…This low alphaamylase activity may be attributed to lesser presence of enzyme and/or to changes occurring in starch during periods of low precipitation during grain development (EVERY et al, 2002;JOHANSSON, 2002). The protein concentration in wheat grain depends on genetic and environmental factors (JOHANSSON, 2002;GUTTIERI et al, 2005). In this study, the protein concentration was influenced by the availability of water during the cultivation cycle (Table 4).…”
Section: Non-irrigatedmentioning
confidence: 65%
“…It was observed higher values of protein in the Non-irrigated Treatment (18.38%) compared to the Irrigated Treatment (15.87%). GUTTIERI et al (2005) also observed a lower concentration of proteins in irrigated wheat compared with those grown in conditions of low water availability.…”
Section: Non-irrigatedmentioning
confidence: 74%
See 1 more Smart Citation
“…종실의 PPO 활성 측정을 위하여 AACCI Approved Methods 22-85.01(AACCI, 2010)에 따라 L-DOPA assay 방법을 이용하였다. 종자 5립을 1.5 ml tube에 5 mM L-DOPA와 50 mM MOPS [3-(N-morrpholino) Habernicht et al, 2002;Souza et al, 2004;Guttieri et al, 2005;Park et al, 2012;Shin et al, 2012). 국수 색깔에 관련된 PPO 활성 및 철 함량 또한 품종 특성 및 환경적 영향을 받는다 (Crosbie and Lambe, 1993;Baik et al, 1994;Gaines et al, 1996;Park et al, 1997;Monasterio and Graham, 2000;Ranum et al, 2006).…”
unclassified